The Impact Of Movement Control Order During Covid-19 Pandemic On Healthcare Utilisation: How Does The Projected Patient Workload Compared To The Actual Number Of Patients In Care? - Amirah Azzeri; Nur Farhan Abdul Hakim; Mohd Hafiz Jaafar; Maznah Dahlui; Sajaratulnisah Othman; Tunku Kamarul Zaman Tunku Zainol Abidin (Faculty of Medicine, Universiti Malaya, 2024)
Indexed by MyCite